Virtual Power Purchase Agreement (VPPA) in Renewable Energy and its Relevance to developing countries like Nepal - Pandey, Ranju; Chaudhary, Deepak (Journey for Sustainable Development and Peace Journal, 2025)
The study discusses virtual power purchase agreements in the renewable energy sector in Nepal. Nepal is rich in renewable energy resources like hydropower as there are more than 6000 rivers with slopes and steep topography. Currently, Nepal is in a position to export power to the cross-boarders (India and Bangladesh). However, there are many obstacles and hurdles in the development of Hydropower in the country. Developing a hydropower plant involves significant financial risks due to its capital-intensive nature, long gestation period, and reliance on external factors like hydrology and regulatory frameworks. In this scenario, if there were a competitive market with the Virtual Power Purchase Agreement, it could reduce the financial risk. It could incentivize national and international investors for financing to produce more renewable energy. Further, VPAA allows it to meet its renewable energy targets easily.